2010
DOI: 10.1021/nl102959k
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric BaTiO3Thin Film Nanogenerator on Plastic Substrates

Abstract: The piezoelectric generation of perovskite BaTiO 3 thin films on a flexible substrate has been applied to convert mechanical energy to electrical energy for the first time. Ferroelectric BaTiO 3 thin films were deposited by radio frequency magnetron sputtering on a Pt/Ti/SiO 2 /(100) Si substrate and poled under an electric field of 100 kV/cm. The metal-insulator (BaTiO 3 )-metal-structured ribbons were successfully transferred onto a flexible substrate and connected by interdigitated electrodes. When periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
446
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 727 publications
(475 citation statements)
references
References 31 publications
4
446
3
6
Order By: Relevance
“…Mechanicalto-electrical transduction mechanisms in piezoelectric materials offer viable routes to energy harvesting in such cases, as demonstrated and analyzed by several groups recently (10)(11)(12)(13)(14)(15)(16)(17). For example, proposals exist for devices that convert heartbeat vibrations into electrical energy using resonantly coupled motions of thick (1-2 mm) piezoelectric ceramic beams on brass substrates (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanicalto-electrical transduction mechanisms in piezoelectric materials offer viable routes to energy harvesting in such cases, as demonstrated and analyzed by several groups recently (10)(11)(12)(13)(14)(15)(16)(17). For example, proposals exist for devices that convert heartbeat vibrations into electrical energy using resonantly coupled motions of thick (1-2 mm) piezoelectric ceramic beams on brass substrates (1).…”
mentioning
confidence: 99%
“…The associated electrical power is substantially less than that required for operation of existing classes of implants, such as pacemakers. Some improvement in performance is possible with thin-film geometries, as demonstrated in bending experiments on devices based on barium titanate (16) and lead zirconate titanate (PZT) (11,12,17). In vivo evaluations are needed, however, to assess the suitability for realistic use and potential for producing practical levels of power.…”
mentioning
confidence: 99%
“…The PZT based implantable energy harvesting devices can also be powered by ultrasonic, which is an effective way of converting acoustic energy into electricity 44. Shi et al reported a piezoelectric ultrasonic energy harvester (PUEH) based on microfabricated PZT diaphragm array with a size of 5 mm × 5 mm, which has advantages of extra wide operation bandwidth and controlled outputs.…”
Section: Materials and Device Designmentioning
confidence: 99%
“…BaTiO 3 thin-film-based NG fabricated by soft lithographic printing technique can produce an output voltage of 1.0 V and current density of 0.19 μA/cm 2 . 19 Although the abovementioned result is outstanding, there is no report about using BaTiO 3 nanotubes to fabricate a NG. As the size of the piezoelectric materials is reduced to the nanoscale, the conversion efficiency of mechanical energy has been found to be improved dramatically, attributing to the larger piezoelectric coefficients and deformations, which are proportional to the generated potential.…”
mentioning
confidence: 99%